Kinetic model of biological oxidation in rotating biological contactors - Chalermraj Thanantaseth; Watanabe, Yoshimasa; Nguyen, Cong Thanh; Samorn Muttamara; Royal Danish Government (Bangkok : Asian Institute of Technology, 1981)
The major problem of the treatment efficiency for nitrification is the existence of BOD5 in the wastewater. The model was developed to explain the phenomena occurring in the rotating biological contactor unit base on the property of substrate diffusion and the degree of zero order biological reaction within the biofilm. The active biofilm are divided into outer layer of heterotrophic and inner layer of nitrifying microorganism due to lower diffusion coefficient but higher biological reaction of organic carbonaceous substrate than the ammonia-nitrogen, and so, the nitrification rate will depend on the oxygen and ammonia-nitrogen concentration, on the nitrifying surface, left from the heterotrophic utilization. Experiments with low influent BOD5 concentration were carried on to prevent oxygen limitation in the heterotrophic layer and to be able to observe the reduction of oxygen penetration into the nitrifying layer. The experimental variables were hydraulic loading, influent BOD5, and the type of organic carbonaceous material. Experimental results show that higher BOD5/N ratio together with higher hydraulic loading caused the lowering in nitrification rate. These were adequate explained by the proposed model.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Sewage -- Purification -- Rotating disc process; Sewage -- Purification -- Nitrogen removal